(untitled) (Research, Society and Development, 2025)
Sepsis is characterized by clinical organ dysfunction resulting from a dysregulated response caused by pathogenic microorganisms. When diagnosed late, it increases the incidence of deaths from septic shock, with the Intensive Care Unit (ICU) being the most likely setting for its development. Worldwide, this infection affects millions of people annually, with the highest prevalence and lethality in developing countries. According to the Department of Informatics of the Unified Health System (DATASUS), through the Hospital Information System (SIH), in Brazil, in 2024, there were 81,765 deaths, with an average mortality rate of 44.40%. Objective: To analyze the scientific literature on sepsis detection and management strategies implemented by the nursing team in the Intensive Care Unit. Methodology: This is an integrative review according to the guidelines outlined by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. The time series covered 2019 to 2024, with 1,761 publications identified. After applying the eligibility criteria, 14 articles and 1 guideline national and 4 international guidelines were selected for analysis.